2014
DOI: 10.1016/j.ijnss.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self-management (DSM) in Omani with type-2 diabetes

Abstract: Self-managementSelf-care Oman Patient education Glycemic control Type-2 diabetes a b s t r a c t Objective: The aim of this study was to assess the status of diabetes self-management (DSM) among Omanis with type-2 diabetes and its relationship with glycemic control and demographic variables. Methods: A correlational descriptive design using questionnaire was conducted with a convenience sample of 266 Omani patients with type-2 diabetes to collect the data. Results: The findings indicated that DSM among the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
4
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 31 publications
7
50
4
5
Order By: Relevance
“…The associated factors of self‐management in our study differ from those of Alrahbi (), Hara et al (), D'Souza et al () and Lin et al (). We found no significant relationship between diabetes self‐management and glycaemic control, similar to the study of Alrahbi (). In addition, our results showed that diabetes self‐management is not associated with age and level of education.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The associated factors of self‐management in our study differ from those of Alrahbi (), Hara et al (), D'Souza et al () and Lin et al (). We found no significant relationship between diabetes self‐management and glycaemic control, similar to the study of Alrahbi (). In addition, our results showed that diabetes self‐management is not associated with age and level of education.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients' healthcare knowledge is related to positive integrated experiences for diabetes treatment, and integrated care can improve the medical relationship of patients and staff and diabetes care knowledge. These results are also similar to those of prospective studies by Alrahbi and Alghenaimi (2017) The associated factors of self-management in this study are the same as those of Alrahbi (2014) and Hara et al (2014), who noted that gender was related to self-management. In addition, male self-efficacy is better than that of females, and males have better health behaviours (Burner, Menchine, Taylor, & Arora, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The overall self-care management level was higher than the average (cumulative percentage=52%). This finding was higher compared to Omani study where the overwhelming majority of participants reported 'never' to the questions regarding following a diabetic meal plan, physical exercise, and self-blood glucose monitoring (Alrahbi, 2014). In addition, the medication adherence proportion was found to be higher by comparison with an Indian study (Arulmozhi and Mahalakshmy, 2014).…”
Section: Reported Self-care Managementmentioning
confidence: 64%